Complicated Dengue Fever and Its Treatment Dilemmas: A Single-Center Experience in Sri Lanka. (13th January 2021) - Jayaweera, D. K.; Subasinghe, S.; De Silva, R. F.; Sanjeewa, W. A. H. P.; Jayawickreme, K. P.
Abstract : Dengue is an arboviral infection that affects humanscausing significant morbidity and mortality in tropical countries. Our first patient who had diabetes presented with shock and was managed as dengue hemorrhagic fever with superadded sepsis which required noradrenalin plus broad-spectrum intravenous antibiotics. The second patient developed severe bradycardia during the ascending limb of the critical phase with hemodynamic stability, which recovered on discharge. Third patient presented with severe and rapid leaking; we used intravenous albumin as an alternative colloid with good outcome. The fourth patient was a pregnant mother at term, and she went into spontaneous labor during the latter half of the critical phase. The fifth patient developed dengue hemorrhagic fever complicated with probable haemophagocytic lymphohistiocytosis. She was treated with intravenous steroids andimmunoglobulin, yet succumbed on day 7. Conclusion . Dengue is an extremely challenging and dynamic disease, which can lead to many unusual complications.A high index of suspicion is key to diagnose and treat promptly.